Sistem Informasi Monitoring Presensi Siswa SMP Negeri 3 Palopo Berbasis website - Hardiana Hardiana; Jumarniati Jumarniati (Patria Artha Technological Journal, 2023)
The problem that exists at SMP Negeri 3 Palopo Kota Palopo is that there is no information system used to convey information to subject teachers, homeroom teachers, and parents regarding student attendance, still using a manual system by recording attendance on paper. One way to reduce errors that occur is to create a website database that will store student attendance data so that the possibility of scattered data will be small, and many errors where still depend on pieces of paper as records, the impact of a manual attendance processing system causes the recapitulation process carried out by teachers in the field of study is less than optimal. In this way, information system design is expected to alleviate and prevent errors that often occur. The design of web-based attendance applications that utilize information technology, student attendance data allows it to be given directly to parents so that handling of problematic students based on attendance can be handled earlier. The concept offered is to provide a forum so that the school and parents can connect in real timeThe type of research used is Research and Development (R & D) which has been developed based on needs. The R&D (Research &; Development) research method is used because this method is in accordance with the research objectives to be achieved, namely making a website-based attendance monitoring information system for SMP Negeri 3 Palopo students. The method used in this research process uses a waterfall approach or model or commonly called a waterfall. Because the purpose of this study is systematic or sequential. The information system in this study has been tested using blackbox testing techniques and the results can be concluded that all components in the system have run in accordance with their functions. The construction of this website as a student attendance monitoring information system at SMP Negeri 3 Palopo can help study teachers and homeroom teachers obtain accurate student attendance data information to help homeroom teachers convey attendance data information to parents better in the future